The Hierarchy of Character Needs in The Novel "Kenduri Arwah" by A.R. Rizal (A Study of Humanistic Psychology) - Dafit Dia Putra (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to describe the hierarchy of character needs in the novel Kenduri Arwah by A.R Rizal. The research method used in this study is the method of content analysis (analysis). The research data are words, sentences and dialogues contained in the novel Kenduri Arwah by A.R Rizal in descriptive form. The data source is the novel Kenduri Arwah by A.R Rizal. The data collection techniques used in this research are (a) reading the novel Kenduri Arwah (b) marking and taking notes, because the data is in the form of text or quotations (c) taking inventory of the data (d) classifying using the data inventory format. This research uses Abraham Maslow's theory of human psychology. The results showed that there was a hierarchy of needs from the main character. Starting from the physiological needs, the need for security, the need for belonging and love, the need for esteem, the need for self-actualization.